Analysis of Service Quality and Occupational Health and Safety Through Customer Satisfaction with the Smooth Operation - Akbar, Bayurezha; Thamrin, M.; Setyawati, Aswanti (Dinasti Publisher, 2025)
Bunkering, as a vital logistics activity, carries high risks such as delays, fuel contamination, and safety incidents that can affect shipping schedules, operational costs, and company reputation. Implementing occupational safety and health (OSH) standards (personal protective equipment, equipment inspections, safe zones, emergency procedures) and international guidelines (ISM Code, SOLAS, ISGOTT, IGF, SIMOP) is necessary to ensure crew safety and build trust among service users. Timely, responsive, safe, and well-documented bunkering services enhance customer satisfaction, which acts as a mediating variable in fostering harmonious cooperation and operational efficiency. The research findings are expected to contribute to improving bunkering service management, customer satisfaction, and operational efficiency of vessels at international ports. Field observations indicate that delays, fuel quality issues, or OSH procedure violations can lead to delays, additional costs, and reputational damage. This study emphasizes the importance of consistent OSH implementation, crew competency enhancement, and optimized coordination among stakeholders to ensure safe, timely, and efficient bunkering services, thereby supporting sustainable vessel operational efficiency. This research employs a quantitative method, SEM-PLS, with 57 respondents. The results indicate that customer satisfaction mediates the relationships between service quality and occupational safety and health, thereby influencing the smooth operation of ships